The Caatinga as a Living Lab: Climate, Resilience and Smart Cities: Lessons from Brazil’s Semi-Arid Region for Global Urban Futures - Fernandes de Araujo, Jayuri Susy; Tejo Cavalcanti, Mônica; Agra, André (Street Art & Urban Creativity, 2025)
This article reflects on the challenges and opportunities of building smart and sustainable cities in semi-arid regions, focusing on the Caatinga biome in Brazil. Drawing on the Strategic Guide for Smart and Sustainable Cities in the Semi-Arid, it emphasizes how climate pressures and socio-environmental vulnerabilities can be transformed into drivers for resilience, innovation, and inclusive governance. Using the quadruple helix as a guiding framework, the Caatinga is positioned as a living lab for testing and advancing urban strategies. The paper highlights its potential contributions to global debates on climate adaptation, urban sustainability, and the future of smart cities.